2004
DOI: 10.1177/0731684404033965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-mold Curing on Package Reliability

Abstract: Silica filled epoxy resins as encapsulation in chip packages reveal a major influence on the reliability and functionality of microelectronic devices. In this study, the resulting effects of postmold curing (PMC) on the thermomechanical and chemical properties of different mold compounds were observed. Polymer systems of the investigated mold compounds were based on two orthocresol novolacs (OCN), one biphenyl and one multifunctional resin (MFR). It could be shown, that longer thermal treatment after curing le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The flexure strength of all EMC specimen increases rapidly after one-time passivation layer curing process. This phenomenon matches the previous research statements [11][12][13]. The increased glass transition could lead to the increase in flexural modulus of EMC.…”
Section: Resultssupporting
confidence: 92%
“…The flexure strength of all EMC specimen increases rapidly after one-time passivation layer curing process. This phenomenon matches the previous research statements [11][12][13]. The increased glass transition could lead to the increase in flexural modulus of EMC.…”
Section: Resultssupporting
confidence: 92%
“…It was expected that after prolonged exposure to high temperatures the polymer chains would break down [3], resulting in a lower glass transition temperature and a lower modulus. However, in literature also studies which show an increase in the glass transition temperature can be found [4]. Preliminary experiments showed that this was also happening to our molding compound.…”
mentioning
confidence: 79%
“…Apart from ref. [4], surprisingly little studies can be found which report this increase in glass transition temperature and accompanied other changes in mechanical properties after prolonged exposure to high temperatures.…”
Section: Introductionmentioning
confidence: 90%
“…The EMC strength may become stable after the 1,000 hours' hightemperature storage test (Xu et al, 2017d). The reason is the high temperature increases the EMC glass transition, and the increased glass transition leads to the EMC flexural modulus increase (Mengel et al, 2004;Zhang et al, 2016). The evaluation work of FOWLP strength also can be implemented by the finite element method, besides the experimental method.…”
Section: Introductionmentioning
confidence: 99%